2019
DOI: 10.1016/j.ygeno.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Parasesarma pictum (Brachyura: Grapsoidea: Sesarmidae) and comparison with other Brachyuran crabs

Abstract: Mitochondrial DNA (mtDNA) is an extrachromosomal genome which can provide important information for evolution and phylogenetic analysis. In this study, we assembled a complete mitogenome of a crab Parasesarma pictum (Brachyura: Grapsoidea: Sesarmidae) from next generation sequencing reads at the first time. P. pictum is a mudflat crab, belonging to the Sesarmidae family (subfamily Sesarminae), which is perched on East Asia. The 15,716 bp mitogenome covers 13 protein-coding genes (PCGs), 22 transfer RNA genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…This result confirmed that Geosesarma belongs to Grapsoidea, Sesarmidae, congruent with the morphological assignments (Ng et al, 2008;Ng, 2017;Ng and Wowor, 2019;Shy and Ng, 2019). All Sesarmidae species cluster into a clade consisting of two sister groups, which was consistent with previous findings (Wang et al, 2019;Li et al, 2020;Lu et al, 2020; Sesarmidae species are most closely related to Gecacinidae, constituting part of the Grapsoidea group, which is in accordance with the results of the studies by Chen et al (2019), Wang et al (2019), Lu et al (2020), and. The mitochondrial phylogenomic analyses including our dataset have shown the divergent phylogenetic status of Grapsidae and Dotilidae (Wang et al, 2019;Li et al, 2020;.…”
Section: Phylogenetic Analysessupporting
confidence: 91%
See 1 more Smart Citation
“…This result confirmed that Geosesarma belongs to Grapsoidea, Sesarmidae, congruent with the morphological assignments (Ng et al, 2008;Ng, 2017;Ng and Wowor, 2019;Shy and Ng, 2019). All Sesarmidae species cluster into a clade consisting of two sister groups, which was consistent with previous findings (Wang et al, 2019;Li et al, 2020;Lu et al, 2020; Sesarmidae species are most closely related to Gecacinidae, constituting part of the Grapsoidea group, which is in accordance with the results of the studies by Chen et al (2019), Wang et al (2019), Lu et al (2020), and. The mitochondrial phylogenomic analyses including our dataset have shown the divergent phylogenetic status of Grapsidae and Dotilidae (Wang et al, 2019;Li et al, 2020;.…”
Section: Phylogenetic Analysessupporting
confidence: 91%
“…While cox1, cox2, atp8, cox3, nad4, and nad4L initiated by the standard ATG codon, atp6, nad3, nad5, nad6, cob, and nad1 (G. penangensis) used ATA, and nad6 (G. faustum) used GTG. Most PCGs, i.e., atp8, atp6, cox3, nad3, nad5, nad4, nad6, nad1, and cox1 (G. penangensis), were terminated by TAA, whereas nad2 used TAG as stop codon, and cox2, cob, and cox1 (G. faustum) terminated by a single T. These incomplete stop codons have been observed in many brachyuran mitogenomes (Wang et al, 2019; and are thought to be completed by posttranscriptional polyadenylation (Ojala et al, 1981).…”
Section: Genome Structure Organization and Compositionmentioning
confidence: 99%
“…From the phylogenetic tree, we found U. borealis and Tubuca arcuata are clustered in one branch with high nodal support value (BI posterior probabilities [PP] ¼ 100, Figure 1). In addition, the relationship among Sesarmidae, Xenograpsidae, Grapsidae, Ocypodidae, Varunidae, Potamidae, and Bythograeidae is also identified and is largely consistent with previous researches (Shen et al 2013;Wang et al 2018aWang et al , 2018b.…”
supporting
confidence: 88%
“…The overlapping start and stop codons of nad genes have been observed in not only fungi but also animals (Franco et al. 2017; Wang et al. 2019), presumably because of the mRNA transcription of these genes has remained coupled across independent lineages.…”
Section: Discussionmentioning
confidence: 99%